The Transmission of Naraphong Charassri’s Creative Concepts of Site-Specific Dance Performance - panomrak, jirayuth (วารสารวิทยบริการ มหาวิทยาลัยสงขลานครินทร์ | Academic Services Journal, Prince of Songkla University; Vol 28 No 1 (2560): Academic Services Journal, Prince of Songkla University, 2017)
The purpose of this research was to study the transmission of Professor Naraphong Charassri, Ph.D.’s creative concepts of site-specific dance performance. Research methodology included studying related document, documentary survey, interviewing the experts, seminar, informational media, fieldwork survey, and group interview. The findings revealed that the creative of contemporary Thai dramatic arts in the field of site-specific dance performance was to fulfill site-specific by choreographer, site or environment or the particular architectural structure by acting as drama stimulators in various ways. The area itself might encompass the meaning in 2 characteristics including space and site. In this particular study, 2 types of area are: 1) common area: the area which does not specify in any particular importance, it includes unlimited boundary by starting from small specific important area and 2) specific area: special area in certain particular way such as historical area, archeological area and educational area. These areas are tremendously significant for fine arts and they are comprised of six dramatic arts including space, time, force, body, movement and form. In addition to those findings, the study of specific area found in creative concepts of site-specific dance performance proposed by Professor Naraphong Charassri, Ph.D could be classified in different types as follows: 1. Specific area based on heritage culture 2. Specific area based on contemporary culture 3. Specific area based on area diversity and context Keywords: specific area of performing arts, Naraphong Charassri, contemporary dramatic arts